EMOTIONAL MATURITY AS A PREDICTOR OF RESILIENCE IN ADOLESCENTS. (International Journal of Food and Nutritional Sciences, 2022)
The present study was aim to find out emotional maturity as a predictor of resilience in adolescents. The sample of 60 adolescents (30 girls and 30 boys) from baramati (maharashtra state) was selected for this study. Emotional maturity scale developed by Dr. Tara Sabapathy (2017) & Resilience scale (2017) developed by Dr. Vijaya Lakshmi and Dr. Shruti Narain was used for data collection. The obtained findings shows that there is positive and significant correlation between emotional maturity and resilience (r=.390** p= 0.01) and emotional maturity is a strong predictor of resilience at adolescents age.